Palms for North Florida - Edwin R. Duke; Gary W. Knox (EDIS)
ENH-1094, a 16-page illustrated factsheet by Edwin R. Duke and Gary W. Knox, provides assistance in selecting cold hardy palms for northern Florida, including sections on growing conditions, maintenance, treating cold damage, and availability. Includes references and a 10-page table showing characteristics of palm varieties suitable for northern Florida. Published by UF Department of Environmental Horticulture, February 2008.